Depression, anxiety and stress among healthcare workers in the context of the COVID-19 pandemic: a cross-sectional study in a tertiary hospital in Northern Vietnam - Thu Pham, Hien; Viet Cao, Tung; Bich Le, Ngoc; T-T Nguyen, Nhung; Thi Ngoc Vuong, Bich; Vu Dieu Pham, Linh; Thu Hoang, Trang; Thi Hanh Pham, Trang; Ngoc Nguyen, Thuy; Thi Thu Bui, Huong; Van Tran, Tho; Thuy Vu, Linh; et al. (Frontiers in Public Health, 2023)
Introduction: The outbreak of coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) had significant effects on the mental well-being in general, particularly for healthcare professionals. This study examines the prevalence of depression, anxiety, and stress, and identify the associated risk factors amongst healthcare workers during the COVID-19 outbreak in a tertiary hospital located in Vietnam. Methods: This cross-sectional study was conducted at a tertiary-level hospital, where Depression Anxiety and Stress Scale 21 (DASS-21) web-based questionnaire were employed. The determinant factors were analyzed by employing multivariate logistic models. Results: The prevalence of depression, anxiety, and stress symptoms were 19.2%, 24.7%, and 13.9%, respectively. Factors such as engaging into shift work during the pandemic, taking care after patients with COVID-19, and staff’s health status were associated with mental health issues among health professionals. In addition, having alternate rest periods were likelihood reduction the risk of stress. Conclusion: The prevalence of mental health problems in healthcare workers during the COVID-19 pandemic was relatively high. Having resting periods could potentially mitigate the development of stress among health professionals. The findings suggest that it should be taken into improving mental health for the health professional population.